"Made in China": the displacement effect of China on Egyptian textile exports. Issue 2 (21st August 2017) - Abu Hatab, Assem
Abstract : Purpose: A growing number of studies indicate that the export growth of China's textiles poses serious threats to many developing countries. The purpose of this paper is to empirically measure the extent to which the export growth of Chinese textiles has come at the expense of Egyptian textiles exports in third importing markets. Design/methodology/approach: To measure this effect, an augmented gravity model equation was estimated using annual data covering the period 1994-2012 on Egyptian and Chinese textile exports to traditional importers of Egyptian textiles. Findings: The empirical results suggest that Egyptian textiles are vulnerable to competitive threat posed by China, especially in the EU and US markets. In contact, Egyptian textile exports have moved hand-in-hand with Chinese textile exports to Asian markets. Moreover, the results suggest that the expiration of the Multi-fiber Agreement in 2005 has exposed Egyptian textile exports to fierce completion with China and resulted in declines in Egypt's textile exports to the world. However, the trade agreements that Egypt signed with the world countries have given Egypt a competitive edge in major importing regions and mitigated the negative impacts of China in the post-2005 period. Finally, the paper argues that unless Egypt adjusts and develops its textile sector in response to such heightened competition from China, Egyptian textile exports undoubtedly would further be negatively impacted. Research limitations/implications: In this study, Egypt's textile products are aggregated to one group and analyzed as a whole, "textile exports." Further research using a more disaggregated level of data would offer deeper insights into the impacts of China on Egyptian textile exports. Originality/value: The contribution of this paper is twofold: first, it adds to the growing literature aiming to understand the impacts of China's growth on developing countries exports by providing a case study of Egyptian textile export sector. Second, the policy implications drawn from this paper could be useful to Egyptian policy makers and stakeholders to address and respond to the competitiveness challenges posed by China to the Egyptian textile industry.